2004
DOI: 10.1111/j.1365-2966.2004.08313.x
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the chemical composition of the Orion nebula based on Very Large Telescope echelle spectrophotometry

Abstract: We present Very Large Telescope (VLT) UVES echelle spectrophotometry of the Orion nebula in the 3100-10 400 Å range. We have measured the intensity of 555 emission lines, many of them corresponding to permitted lines of different heavy-element ions. This is the largest set of spectral emission lines ever obtained for a Galactic or extragalactic H II region. We have derived He + , C 2+ , O + , O 2+ and Ne 2+ abundances from pure recombination lines. This is the first time that O + and Ne 2+ abundances have been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
428
10
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 288 publications
(497 citation statements)
references
References 70 publications
57
428
10
2
Order By: Relevance
“…The different estimations of the amount of C locked up in dust grains in the local interstellar medium show a rather large variation depending on the abundance determination methods applied (see Jenkins 2014). Assuming the quantities complied by Jenkins (2014) we find that the gas+dust C/H ratios in the Orion Nebula would be between 0.09 to 0.26 dex larger than the ionized gas phase values determined by Esteban et al (2004). However, some degree of destruction of C-bearing dust particles is likely to be acting in ionized nebulae and the assumption of depletion factors of the neutral diffuse interstellar medium may not be appropriate for an ionized nebula.…”
Section: The C/o Vs O/h Relationmentioning
confidence: 96%
See 1 more Smart Citation
“…The different estimations of the amount of C locked up in dust grains in the local interstellar medium show a rather large variation depending on the abundance determination methods applied (see Jenkins 2014). Assuming the quantities complied by Jenkins (2014) we find that the gas+dust C/H ratios in the Orion Nebula would be between 0.09 to 0.26 dex larger than the ionized gas phase values determined by Esteban et al (2004). However, some degree of destruction of C-bearing dust particles is likely to be acting in ionized nebulae and the assumption of depletion factors of the neutral diffuse interstellar medium may not be appropriate for an ionized nebula.…”
Section: The C/o Vs O/h Relationmentioning
confidence: 96%
“…In this case, there seems to be no discrepancies between the methods for determining the O 2+ abundance used by both research groups. The spectra of some of the sample objects also show permitted lines of other heavy-element ions as N i, N ii, N iii, O i and/or Si ii, but they are produced by fluorescence and can not be used to derive reliable abundance values (see Esteban et al 1998Esteban et al , 2004.…”
Section: Ionic Abundances and Abundance Discrepancymentioning
confidence: 99%
“…We have used intensity ratios of several selected emission lines of spectra of Galactic H ii regions published by Esteban et al (2004Esteban et al ( , 2013 and García-Rojas et al (2004 Esteban et al (2013) and calculated by Copetti et al (2007). The distances are based on kinematical or photometrical methods and have typical uncertainties of less than 1 kpc (e.g.…”
Section: Observational Datamentioning
confidence: 99%
“…Open black circles refer to PN located in the MWG disk and taken from our extended sample, red filled circles represent H II regions from Garnett (1995Garnett ( , 1997Garnett ( , 1999, MWG disk stars from Gustafsson et al (1999) are shown with blue filled circles, MWG metal poor halo stars from Akerman et al (2004) are indicated with orange filled diamonds, green open squares and diamonds indicated LMC and SMC PN by Stanghellini et al (2005Stanghellini et al ( , 2009) respectively, and red filled squares correspond to low metallicity dwarf galaxies by Berg et al (2016). The maroon filled triangle and magenta filled diamond represent Orion (Esteban et al 2004) and the Sun (Asplund et al 2009), respectively. of 3rd dredge-up, which elevates C, and hot bottom burning, which does likewise to N. However, explanations of PN abundance patterns based upon progenitor masses is typically not included.…”
Section: Introductionmentioning
confidence: 99%
“…Open black circles refer to PN located in the MWG disk and taken from our extended sample, filled red squares represent Galactic H II regions from Deharveng et al (2000) and the filled magenta triangle shows the solar position (Asplund et al 2009). The position of Orion (Esteban et al 2004) is indicated. different research groups and evaluate each set of models based upon how well they appear to explain the observed abundances.…”
Section: Introductionmentioning
confidence: 99%